Optimasi Proses Demineralisasi Cangkang Rajungan (Portunus pelagicus) Kajian Suhu dan Waktu Demineralisasi - Martati, Erryana; Susanto, Tri; Yunianta, Yunianta; Efendi, Zohan (Fakultas Teknologi Pertanian Universitas Brawijaya, 2002)
The aim of the research was to study the effect of temperature and the time exposure of deproteinization toward demineralized crab shell characteristic. This experiment was done in various temperature i.e. 650 C, 750C and 850 C and time exposure i.e. 2, 6 and 10 hours. The results showed the temperature treatment had influence toward ash content, calcium content, protein content and the yield very significantly. The time exposure treatment had influence toward ash content, calcium content and protein content very significantly. Interaction both of that had influence toward calcium content only. The best treatment was selected by Multiple Attributes Methods. It was demineralizalition at temperature 85 0C for 15 hours, The characteristics of demineralized shell were ash content 0,277%, calcium content 0,123%, water content 5,364 %, protein content 30,3% and the yield 13,21%. This treatment gave mineral content and calcium content of demineralized shell that fulfilled the chitin standard.Key words: chitin, demineralization, crab shell